Interrelations between the Oppel-Kundt- and the T-illusion. (July 2022) - Landwehr, Klaus
In order to investigate interrelations between the Oppel-Kundt- and the T-illusion, T-type figures, comprised of one dotted and one empty line (demarcated by its endpoints), separated by a gap of variable size, and rotated to oblique orientations, were judged with regard to the lengths of the two extents. The T-illusion (overestimation of the length of the undivided line) was greater for a T with a dotted undivided line and a small gap. When the divided line was dotted, the illusion vanished at a small gap and reversed at a larger one. Findings are interpreted to mirror activities of a neural T-schema as well as orientation- and density-sensitive neurons.